Economic and Institutional Determinants of Export Growth in Asean: Evidence from a Regional and Bilateral Perspective - Prirayani, Jagat (Jurnal sosial dan sains, 2025)
The ASEAN region has emerged as a vital hub in global trade, yet the determinants of its export performance—particularly from both regional and bilateral perspectives—remain underexplored in a cohesive empirical framework. The study investigates factors affecting export growth in the ASEAN economy over the sample period of 1996–2023 from a regional and bilateral trade flows perspective. The ASEAN countries sample includes Indonesia, Singapore, Malaysia, Thailand, and the Philippines. We employ panel regression techniques to examine the impact of GDP growth, inflation, globalization, political stability, and exchange rate growth on export growth. The findings show that GDP growth and exchange rate growth positively drive export growth, while inflation reduces export growth. In contrast, globalization, political stability, and COVID-19 have not significantly affected export growth in the region. Furthermore, at the bilateral level, the findings are more heterogeneous. Among all variables, GDP growth and exchange rate growth dominate as significant determinants of bilateral export trading in the region. Overall, the results demonstrate that a one-size-fits-all policy cannot explain the trade dynamics of ASEAN; it requires country-specific policies with structural reforms to enhance regional integration.